The coming of the Third Reich - Evans, Richard J. 1947- (The Penguin Press, 2004)
Publisher description: From one of the world's most distinguished historians, a magisterial new reckoning with Hitler's rise to power and the collapse of civilization in Nazi Germany. In 1900 Germany was the most progressive and dynamic nation in Europe, the only country whose rapid technological and social growth and change challenged that of the United States. Its political culture was less authoritarian than Russia's and less anti-Semitic than France's; representative institutions were thriving, and competing political parties and elections were a central part of life. How then can we explain the fact that in little more than a generation this stable modern country would be in the hands of a violent, racist, extremist political movement that would lead it and all of Europe into utter moral, physical, and cultural ruin? There is no story in twentieth-century history more important to understand, and Richard Evans has written the definitive account for our time. A masterful synthesis of a vast body of scholarly work integrated with important new research and interpretations, Evans's history restores drama and contingency to the rise to power of Hitler and the Nazis, even as he shows how ready Germany was by the early 1930s for such a takeover to occur. With many people angry and embittered by military defeat and economic ruin; a state undermined by a civil service, an army, and a law enforcement system deeply alienated from the democratic order introduced in 1918; beset by the growing extremism of voters prey to panic about the increasing popularity of communism; home to a tiny but quite successful Jewish community subject to widespread suspicion and resentment, Germany proved to be fertile ground in which Nazism's ideology of hatred could take root. The first book of what will ultimately be a complete three-volume history of Nazi Germany, The Coming of the Third Reich is a masterwork of the historian's art and the book by which all others on this subject will be judged